Studies on the lactic-fermentation of sugar apple (Annona squamosa L.) puree - Tien, Y. Y.; Ng, C. C.; Chang, C. C.; Tseng, W. S.; Kotwal, S.; Shyu, Y. T. (Journal of Food and Drug Analysis, 2005)
Sugar apple (Annona squamosa L.) is a fruit tree of economic importance in Taiwan, with the fruit primarily consumed fresh. Overproduction in recent years, coupled with short shelf life and other practical issues, make practical the research into uses for sugar apples in formats other than fresh. This study presents an exploration of lactic-fermented sugar apple products. The product has a unique sweet aroma and a test panel found its texture to be appealing. For this study, sugar apple puree was used as the substrate for fermentation using mixed starters in a ratio 1:1 or 1:1:1. The high total soluble solid nature (20.5 +/- 4.33 degrees Brix) of sugar apple puree as compared to that of mixed fruit juice (lower than 10 Brix) indicates its potential to be used in fermentation. Following fermentation, the properties and effects of different starter inoculations were recorded and discussed. Fermentation achieved a pH value of 3.8 after 60 hr. The performance of fermented product in the DPPH (alpha,alpha-diphenyl-beta- picrylhydrazyl) decreased from 92% to 78% after 48 hr, followed by a stationary state. Fermented sugar apple puree and fresh sugar apple juice blended in a ratio of 2:8 delivered the highest DPPH scavenging efficiency (88%) and iron chelating ability (49%). The relatively high values of these properties offer the potential for sugar apple juice to be further developed as a novel functional food. Such a development would surely help to ease recent overproduction problems.
Keywords: annonaceae; DPPH scavenging; Fermentation; Lactobacillus

Rapid molecular identification of freshly squeezed and reconstituted orange juice - Ng, C. C.; Chang, C. C.; Wu, I. C.; Kotwal, S.; Shyu, Y. T. (International Journal of Food Science and Technology, 2006)
This work presents a rapid and accurate molecular approach in the identification of freshly squeezed and reconstituted orange juice. Primers were designed based on the 18S and internal transcribed spacer (ITS) region. The findings indicated that self-made freshly squeezed orange juice heated to 80 degrees C for 30 s caused damage to DNA integrity, thus failing in amplification by primer 18S-ITSe, which gives a polymerase chain reaction product of 2081 bp, whereas primer 18S-ITSf, fragment length 2421 bp, could only be seen in heating conditions less stringent than 70 degrees C, 15 s. This new DNA integrity-dependent method has potential applications in identifying adulteration of freshly or processed orange juice.
Keywords: adulteration; citrus; DNA degradation; molecular detection; reconstituted juice